BLACKS' PROTEST SONGS: THE EXPRESSION OF LYNCHING AND CRIMINAL JUSTICE SYSTEM IN THE USA - Lawolyo, Dave Gideon Shermant; Rasiah, Rasiah (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
The protest has become the main, dominant inner-structure, and predominant theme not only in black writings, especially literary works, like; novels and poetry but also in the song writings. The protest is rooted in black slavery and racism has been felt and may continue to be felt throughout U.S. history. This article sought to indicate the mode of racism and ways of black in resisting it reflected in three protest songs written by blacks. Looking at the three decades of protest songs, three are standing out as important examples for this study: “Strange Fruit” (1937), “Say It, I’m Black and I’m Proud” (1968), and “Blue Lights” (2018). These protest songs are consistent in messaging the racism in the criminal justice system and black resistance against it over time. Critical race theory enables how racism as a legal, cultural, and political condition is reproduced and maintained, primarily in the US context. Strange Fruit portrays about lynching in the era of Jim Crow. They were tortured and lynched, reflecting how black people were experiencing discriminatory treatments and extrajudicial punishment after the civil war. Say It, I’m Black and I’m Proud portrays racial inequality in the post-Civil Rights Movement. Whites are still privileged and blacks are undervalued. More advances, Blue Lights portrays the concern of black people in facing racism that affects institutions like law enforcement, which leads to arbitrary shooting of black people in crime scenes in the present time. Taken together, the songs reflect the dynamic nature of racism, as well as the shifting mode and attitude of blacks in struggling against racism from the past up to the present time in the US from passive, radical, and subtler